Widening participation in medicine in the UK and Australia: An international comparison of policy, process and experience - Coyle, Maeve (Curtin University, 2022)
'Medical education is concerned with developing best medical practice in supporting diverse, culturally competent physicians to deliver excellent patient care. Recent policy and practice aims to encourage applicants from disadvantaged backgrounds into the profession via widening access (WA) and widening participation (WP) initiatives. However certain groups remain under-represented in medicine worldwide. For those who do successfully navigate their way through the selection process, we know little about this journey, and how these policies and practices operate ‘on the ground’. The UK and Australia share historical similarities in the trajectory of their health and education policies, as well as significant differences in more recent policy drivers linked to WP. These two countries make for good systems of comparison in exploring how WP medical students and medical school staff experience and perceive WP policy and practice. Research approaches used qualitative methods (participant interviews and document analysis) within a comparative case study design to explore WA and WP within and between each context. Underpinned by a critical constructivist paradigm, theoretical frameworks applied in data analysis include a critical discourse analysis of national policy aimed at WP, an actor-network theory perspective on institutional WA and WP policy and processes, and a narrative inquiry of WP student experiences. The aim was to achieve a better understanding of how widening participation in medicine is interpreted and experienced at national (macro), institutional (meso) and individual (micro) levels in each context, with a view to encouraging and supporting meaningful changes in the philosophies, policies and practices of WP. Findings suggest that universities and medical schools are replete with competing priorities that are often in tension with practices aimed at greater inclusion. Opening up medicine to embrace diversity will not happen without the deconstruction of entrenched processes and practices, explicit recognition of context, and the equal engagement of all stakeholders.